Isolasi dan Skrining Bakteri Selulolitik pada Feses Luwak - Kesuma, I Putu Eko Arymanto Wira; Wijaya, I Nyoman; Sritamin, Made (Nandur; Vol 1 No 3 (2021), 2021)
Civet ( Paradoxurus hermaphroditus ) are carnivorous animals, but also often eat fruit and one of them is coffee cherries. The coffee cherries that are eaten are not completely digested, so the coffee beans come out with the civet feces. In the civet digestion there are various kinds of bacteria that help the digestive process, one of them is cellulolytic bacteria. It is possible that coffee beans in civet feces contain cellulolytic bacteria.This study aims to determine the presence of cellulolytic bacteria in civet feces. The results of bacterial isolation in civet feces obtained 6 isolates that had different morphological characters. Cellulolytic bacteria screening results showed that 2 out of 6 isolates were positive as cellulolytic bacteria, namely FL2 isolate with a cellulolytic index of 2.38 (high reaction) and FL3 isolate with a cellulolytic index of 1.24 (medium reaction). The isolates FL2 and FL3 had different morphological characters in colony shape, margins and color, but had similarities in elevation, gram color and cell shape.